Improved Catalytic Activity of Ruthenium–Arene Complexes in the Reduction of NAD - Soldevila-Barreda, Joan J; Bruijnincx, Pieter C. A; Habtemariam, Abraha; Clarkson, Guy J; Deeth, Robert J; Sadler, Peter J (Organometallics, 2012)
A series of neutral RuII half-sandwich complexes of the type [(η6-arene)Ru(N,N′)Cl] where the arene is para-cymene (p-cym), hexamethylbenzene (hmb), biphenyl (bip), or benzene (bn) and N,N′ is N-(2-aminoethyl)-4-(trifluoromethyl)benzenesulfonamide (TfEn), N-(2-aminoethyl)-4-toluenesulfonamide (TsEn), or N-(2-aminoethyl)methylenesulfonamide (MsEn) were synthesized and characterized. X-ray crystal structures of [(p-cym)Ru(MsEn)Cl] (1), [(hmb)Ru(TsEn)Cl] (5), [(hmb)Ru(TfEn)Cl] (6), [(bip)Ru(MsEn)Cl] (7), and [(bip)Ru(TsEn)Cl] (8) have been determined. The complexes can regioselectively catalyze the transfer hydrogenation of NAD+ to give 1,4-NADH in the presence of formate. The turnover frequencies (TOF) when the arene is varied decrease in the order bn > bip > p-cym > hmb for complexes with the same N,N′ chelating ligand. The TOF decreased with variation in the N,N′ chelating ligand in the order TfEn > TsEn > MsEn for a given arene. [(bn)Ru(TfEn)Cl] (12) was the most active, with a TOF of 10.4 h–1. The effects of NAD+ and formate concentration on the reaction rates were determined for [(p-cym)Ru(TsEn)Cl] (2). Isotope studies implicated the formation of [(arene)Ru(N,N′)(H)] as the rate-limiting step. The coordination of formate and subsequent CO2 elimination to generate the hydride were modeled computationally by density functional theory (DFT). CO2 elimination occurs via a two-step process with the coordinated formate first twisting to present its hydrogen toward the metal center. The computed barriers for CO2 release for arene = benzene follow the order MsEn > TsEn > TfEn, and for the MsEn system the barrier followed bn < hmb, both consistent with the observed rates. The effect of methanol on transfer hydrogenation rates in aqueous solution was investigated. A study of pH dependence of the reaction in D2O gave the optimum pH* as 7.2 with a TOF of 1.58 h–1 for 2. The series of compounds reported here show an improvement in the catalytic activity by an order of magnitude compared to the ethylenediamine analogues.